2023
DOI: 10.1126/sciadv.adg4923
|View full text |Cite
|
Sign up to set email alerts
|

A customized MOF-polymer composite for rapid gold extraction from water matrices

Abstract: With the fast-growing accumulation of electronic waste and rising demand for rare metals, it is compelling to develop technologies that can promotionally recover targeted metals, like gold, from waste, a process referred to as urban mining. Thus, there is increasing interest in the design of materials to achieve rapid, selective gold capture while maintaining high adsorption capacity, especially in complex aqueous-based matrices. Here, a highly porous metal-organic framework (MOF)–polymer composite, BUT-33–pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…5A). 48 In contrast, the PXRD pattern of PCS-CZ-B-DCM adsorbed in the dark showed no peak for Au(0), indicating that the reduction of Au( iii ) to Au(0) by the PCS-CZ-B-DCM requires visible light irradiation. The PCSs@chitosan can still reduce Au( iii ) to Au(0) under dark conditions due to the redox reaction between the amino and hydroxyl groups in the PCSs@chitosan and Au( iii ).…”
Section: Resultsmentioning
confidence: 96%
“…5A). 48 In contrast, the PXRD pattern of PCS-CZ-B-DCM adsorbed in the dark showed no peak for Au(0), indicating that the reduction of Au( iii ) to Au(0) by the PCS-CZ-B-DCM requires visible light irradiation. The PCSs@chitosan can still reduce Au( iii ) to Au(0) under dark conditions due to the redox reaction between the amino and hydroxyl groups in the PCSs@chitosan and Au( iii ).…”
Section: Resultsmentioning
confidence: 96%
“…On the one hand, the amounts of adsorption sites might increase with more polymer loading and the adsorption capacity might also increase. On the other hand, when the polymer loading continued increasing to more than 35.9%, the extra guest copolymer molecular might block the pores of MIL-53, and the amounts of exposed adsorption sites might be reduced, so the adsorption capacity started to decreased . The results showed that the composites stirred for 6 h before polymerization exhibited the optimal adsorption property, and its corresponding polymer loading amount was 35.9 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, adsorption has been recognized as a feasible and environmentally friendly strategy due to its easy operation, low cost, high efficiency, and green process . Recently, numerous novel gold adsorbents with high capacities have already been explored, such as metal–organic frameworks (MOFs), porous organic polymers (such as covalent organic frameworks, porous aromatic frameworks, , porous organic polycarbene, and porous porphyrin polymer , ), functionalized silicas, polysaccharides, chelating resins, and modified fibers . Although these adsorbents were effective in capturing gold from electronic waste, their tedious synthetic procedures, high-cost precursors, poor selectivity, and slow kinetics of some of them impede their practical applications.…”
Section: Introductionmentioning
confidence: 99%